Fairness in Dismissal for Business Reasons in Indonesia - SANTOSO, Budi (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
This article aims to analyze the fairness in dismissal for business reasons under labor practice and law in Indonesia. This is important as an evaluation material for the future regulation of the dismissal. By using statutory and case approaches, there are several steps reflect fairness in exercising the dismissal, i.e: (1) the circumstances justifying the dismissal; (2) the exercising dismissal as a last resort; (3) the negotiations with worker or workers’ representatives was done to settle the dismissal; (4) the employer's obligation to notify the decision of dismissal to workers; and (5) paying the worker’s entitlement upon dismissal. However, the absence of the employer’s obligation to make selection criteria for the dismissal and to notify the decision of dismissal to government has reduced the fairness aspect of dismissal’s procedure for business reasons.